(untitled) (International Journal of Engineering and Computer Science, 2017)
Virtualism is a new style of thinking and acting that human kind began moving toward it. Reducing time and nearing place in virtual space produce new patterns of thinking and acting. My article aims to two things; first: it wants to understand the overall global transformation to virtual system, reality and language. Second: then to indicate that philosophical system imposed by philosophers of postmodernism on the scene of world philosophy may has been rotted as a result to the changing in cultural structure.